The Impact of Technological Transformation on the Realm of Modern Business Management - Alomari, Mohamed Qasim Mohamed (Eximia, 2023)
This research study aimed to explore the ever-changing world of management, documenting the significant influence of the ‘Technological Transformation’ (Also referred to as ‘Digital Transformation’) witnessed by the present era. The study carried out a thorough review of the advantages and difficulties that accompanied this unprecedented transformation. Moreover, this study highlighted the practical influence of technology across a vast spectrum of enterprises and sectors using a wide range of studies from the relevant literature. Over and above, this qualitative study implemented the ‘Integrative Research Approach’ (IRA) for the sake of obtaining data from the targeted population, analyzing the collected data, and extracting the findings concerned. Supplementarily, the study found that the process of technological transformation involves not just automating operations but also changing businesses’ models, customer expectations, and the processes themselves. Likewise, it was found that digital businesses produce value and create an accelerating revenue by means of extensive digital linkages between people, locations, systems, and objects. Conjointly, the study revealed that the majority of contemporary organization, Organizations, regardless of their areas of competence and work, may leverage digital technologies and strategy to establish a successful position for both themselves and their industrial sector/s. as a matter of fact, the current study emphasized that the next phase in the growth of the national and international economies is the potential that digital/technological transformation unlocks. Finally, the study’s findings asserted that the society that will live in a completely altered environment is transformed by the integration of all developing technologies. Production of goods, corporate operations, and organizational leadership are shifting toward a heavy reliance on new technologies, supporting applied Information Technology (IT) techniques (software, hardware, and procedures), and expanding digital communication channels. On the same line, the study concluded that in order to maintain the stability and strength of our societies, we must continuously examine, evaluate, and develop this new, highly complex reality that the digital transformation has formed. Finally, it is hoped that the previously mentioned findings would assist organizations of different fields of work in making successful, reliable, and accurate decisions. Similarly, it is also hoped that the revealed findings would pave the way for the organizations of interest to create and further implement innovative, actionable, purpose-filled, Long-term and forward-focused, consistent, concrete, inclusive, and well-informed strategies which would eventually enable them to act as a compass in the nowadays’ complex landscape of technological revolutions.